Characteristics of ALD‐ZnO Thin Film Transistor Using H2O and H2O2 as Oxygen Sources (Adv. Mater. Interfaces 15/2022). Issue 15 (23rd May 2022) - Yang, Jun; Bahrami, Amin; Ding, Xingwei; Lehmann, Sebastian; Kruse, Nadine; He, Shiyang; Wang, Bowen; Hantusch, Martin; Nielsch, Kornelius
Abstract : Characteristics of ALD‐ZnO Thin Film Transistor In article number 2101953, Jun Yang, Amin Bahrami, Kornelius Nielsch, and co‐workers report that during atomic layer deposition (ALD)‐ZnO process, H2 O2 provides an oxygen‐rich environment inducing less oxygen vacancies into the ZnO thin film. After applying a bias stress of 10 V for 3600 s, the threshold voltage shift for H2 O2 ‐ZnO thin film transistor is 0.13 V.